Pengaruh Copywriting “Kaya Ada Manis-Manisnya” pada Konten Promosi Le Minerale terhadap Keputusan Pembelian Konsumen - Novita Lestiani; Hudi Santoso; Suparman; Nabhila Manisya; Anggi Widia Khairunnisa (Bahasa Indonesia, 2025)
The influence of creative copywriting in promotional content has grown increasingly significant in today’s competitive market. This study aims to explore how the copywriting phrase “Kaya Ada Manis-Manisnya” in Le Minerale’s promotional content impacts consumer purchasing decisions. Using the AIDA model (Attention, Interest, Desire, Action) and consumer purchasing decision theory, the research analyzes the effects of this copywriting on consumer motivation, perception, attitude, reference groups, and social status. A quantitative descriptive-analytic approach is employed, with a survey conducted among 93 students from the Digital Communication and Media at IPB University’s Vocational School. Data analysis through simple linear regression reveals a significant influence of Le Minerale’s copywriting on purchasing decisions, with the model explaining 67% of the variation in purchase behavior. This research highlights the importance of emotionally engaging copywriting in building brand preference and provides insights for Le Minerale to enhance future marketing strategies. Furthermore, effective copywriting can enhance consumer trust, particularly when it resonates with personal and social value.